The cognitive effects of al-qur’an memorization: a systematic review of impacts on memory, academic performance, and broader cognitive functions - Novianita Achmad; Sarson W. Dj. Pomalato; Maryam Rahim; Novianty Djafri; Evi Hulukati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This systematic review critically synthesizes 30 empirical studies to evaluate the cognitive consequences of Al-Qur'an memorization (hifdh), addressing a significant gap in differentiating between domain-specific memory gains and broader cognitive enhancement. Utilizing a rigorous selection process from the Semantic Scholar corpus, the study examines the impact on core memory functions, the potential for transfer to academic and executive domains, and the efficacy of various pedagogical interventions. The results demonstrate compelling evidence for